Managerial Innovation and Organizational Creativity in Education: a Comparative Study of Turkey and Ukraine - Yildirim, Ahmet (Journal of Vasyl Stefanyk Precarpathian National University, 2026)
This study examines the relationship between managerial innovation and organizational creativity in schools and tests whether the strength of this relationship differs between Turkey and Ukraine. Using a cross-national, quantitative correlational design, data were collected in the 2025–2026 academic year from 569 teachers (Turkey n=282; Ukraine n=287) with the Managerial Innovation Scale and the Organizational Creativity Scale. Because subgroup distributions were uneven, nonparametric analyses were applied, Spearman’s rho to estimate associations, Fisher’s z to compare correlations across countries, and Mann–Whitney U and Kruskal–Wallis H tests (with Bonferroni post hoc comparisons) to examine group differences. Results showed a strong positive association between managerial innovation and organizational creativity overall. The relationship was moderate in Turkey and stronger in Ukraine and the difference was significant. Ukrainian teachers reported higher levels of both managerial innovation and organizational creativity, and significant differences emerged by gender, professional seniority, and teaching field. Findings suggest that innovation-oriented leadership, school autonomy, and an innovation-supportive climate can strengthen teachers’ creative capacities, highlighting the role of system-level reforms in enabling creative school cultures. Practically principals can foster creativity by involving teachers in decisions, lowering organizational barriers, and recognizing experimentation and collaboration. For policymakers, the cross-national pattern implies that decentralization and sustained professional support may amplify the creativity gains associated with managerial innovation.